MSc Grant schemes - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
Two rounds have been implemented in Ethiopia and 1 round in Vietnam, while the first round in Bangladesh started in 2019 and will continue in 2020. These lead to increased partnership with local young scientists and their research institutes/universities.